Notes on the IV CLUP - Latin American Colloquium on Urbanization and Patrimonialization, Argentina - Arias, Johanna (2024)
The CLUP – Latin American Colloquium on Urbanization and Patrimonialization – is a biennial academic event that brings together researchers in Geography, human and social sciences from Latin America and the Caribbean, a favorable space for the dissemination of topics and theoretical-methodological debate related to land uses, urban-rural dynamics, and the socialization of the natural environment on the continent. The event is promoted by GECIPA (CNPq Research Group on Cities and Patrimonialization in Latin America and the Caribbean), which belongs to the Department of Geography of the University of Brasilia (UnB) and was founded in 2011, under the coordination of Professor Everaldo Batista da Costa. The IV was held at the National University of the South, between September 26 and 28, 2024, bringing together about 130 researchers from universities and other institutions in Brazil, Mexico, Chile, Argentina and Costa Rica. The event featured a total of 13 panels, in which 78 papers were presented, which allowed for reflection and proposals for possible paths for the construction of socio-spatial justice and for the criticism and confrontation of socio-spatial inequalities, which involve rural cities in Latin America and the Caribbean.